Migration and Economic Growth: a 21st Century Perspective - Cat Moody (New Zealand Government, The Treasury, 2006)
While there is extensive literature on the determinants of migration and its microeconomic effects, the New Zealand theoretical or empirical literature specifically examining the effects of migration on economic growth is not as comprehensive. In New Zealand there has been an implicit underlying assumption that immigration is good for economic growth, as evidenced by the attempted use of immigration to resolve particular labour market problems. This paper uses the growth accounting policy framework to discuss the mechanisms through which immigration can impact economic growth. It reviews the contemporary literature with a view to identifying how immigration policy may be adjusted to improve the potential returns to growth from immigration in New Zealand.
Keywords: F22; J61; O49; O56; 330; Migration; immigration; emigration; economic growth; growth accounting framework; New Zealand